Numerical modeling of ultrasound propagation in heterogeneous media using a mixed domain method - Jing, Yun; Gu, juanjuan (The Journal of the Acoustical Society of America, 2018)
A mixed domain method (MDM) is presented in this paper for modeling one-way linear/nonlinear wave propagation in biological tissue with arbitrary heterogeneities, in which sound speed, density, attenuation coefficients, and nonlinear coefficients are all spatial varying functions. The MDM is based on solving a Westervelt-like equation. We validated the algorithm by studying a number of one-dimensional and two-dimensional problems. Overall, this study demonstrates that the MDM is a computationally efficient and accurate method when used to model wave propagation in biological tissue with relatively weak heterogeneities. We also proposed methods to improve the algorithm for moderately heterogeneous media.